Hepatitis E virus infection in dromedaries, North and East Africa, United Arab Emirates, and Pakistan, 1983–2015 - Rasche, A.; Saqib, M.; Liljander, Anne M.; Bornstein, S.; Zohaib, A.; Renneker, S.; Steinhagen, K.; Wernery, R.; Younan, M.; Gluecks, Ilona V.; Hilali, Mosaad; Musa, B.E.; et al. (Centers for Disease Control and Prevention, 2016)
A new hepatitis E virus (HEV-7) was recently found in dromedaries and 1 human from the United Arab Emirates. We screened 2,438 dromedary samples from Pakistan, the United Arab Emirates, and 4 African countries. HEV-7 is long established, diversified and geographically widespread. Dromedaries may constitute a neglected source of zoonotic HEV infections.